2021
DOI: 10.1111/ejn.15171
|View full text |Cite
|
Sign up to set email alerts
|

Glial expression of DmMANF is required for the regulation of activity, sleep and circadian rhythms in the visual system of Drosophila melanogaster

Abstract: DmMANF, Drosophila melanogaster mesencephalic astrocyte-derived neurotrophic factor (DmMANF) is an evolutionarily conserved orthologue of mammalian MANF. This neurotrophic factor exerts many functions in the Drosophila brain, particularly those dependent on glial cells. As we found in our earlier study, downregulation of DmMANF in glia induces degeneration of glial cells in the first optic neuropil (lamina) where DmMANF abundance is especially high. In the present study, we observed that changes in the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…However, we did not observe phenotypic effect in a control line in which Dicer2 protein was expressed alone, which indicates that the changes were related to the DmMANF deficiency. Interestingly, our other studies showed that overexpression of DmMANF in astrocyte-like glia results in abnormal arborisation of PDF-expressing neurons (Walkowicz et al, 2021). The finding rises the question of whether the morphological changes of PDFpositive neurons are related to disturbances in the expression of DmMANF specifically in tim-positive glia.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, we did not observe phenotypic effect in a control line in which Dicer2 protein was expressed alone, which indicates that the changes were related to the DmMANF deficiency. Interestingly, our other studies showed that overexpression of DmMANF in astrocyte-like glia results in abnormal arborisation of PDF-expressing neurons (Walkowicz et al, 2021). The finding rises the question of whether the morphological changes of PDFpositive neurons are related to disturbances in the expression of DmMANF specifically in tim-positive glia.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, our other studies showed that overexpression of DmMANF in astrocyte-like glia results in abnormal arborisation of PDF-expressing neurons ( Walkowicz et al, 2021 ). The finding rises the question of whether the morphological changes of PDF-positive neurons are related to disturbances in the expression of DmMANF specifically in tim -positive glia.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Glial cells contribute to circadian rhythms and regulating the behavior of flies ( Drosophila melanogaster ). Walkowicz and colleagues show that ensheathing‐ and astrocyte‐like glia in flies utilize mesencephalic astrocyte‐derived neurotrophic factor (DmMANF, an evolutionarily conserved ortholog of mammalian MANF) to regulate sleep and circadian rhythms (Walkowicz et al, 2021). Furthermore, they find that DmMANF regulates the circadian rhythms of the Na + /K + ‐ATPase α‐subunit within glia themselves.…”
mentioning
confidence: 99%